2023
DOI: 10.1007/s00394-023-03103-1
|View full text |Cite
|
Sign up to set email alerts
|

Calcifediol: a review of its pharmacological characteristics and clinical use in correcting vitamin D deficiency

Abstract: Background In addition to the role of vitamin D in bone mineralization, calcium and phosphate homeostasis, and skeletal health, evidence suggests an association between vitamin D deficiency and a wide range of chronic conditions. This is of clinical concern given the substantial global prevalence of vitamin D deficiency. Vitamin D deficiency has traditionally been treated with vitamin D 3 (cholecalciferol) or vitamin D 2 (ergocalciferol). Calcifediol (25-hydroxyvitamin D 3 ) has recently become available more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…As a steroid hormone, VD, obtained from food, supplements, and sunlight exposure without the biological activity of vitamins D2 or D3, is rapidly hydroxylated by 25-hydroxylase in the liver to form 25-hydroxyvitamin D (25(OH)2D calcitriol), 152 which is synthesized and bound to allow the VD-binding protein to circulate, where it is hydroxylated by the kidneys to produce active 1α,25 dihydroxy VD (calcitriol). 153 The classical biological role of estriol as the active form of VD in controlling calcium and phosphate metabolism in bone health, 154 and previous studies have revealed that VD also regulates cell differentiation, strengthens the immune system, reduces oxidative stress and inflammation, and has neurotrophic effects in addition to its role in bone development.…”
Section: Vitamin Dmentioning
confidence: 99%
“…As a steroid hormone, VD, obtained from food, supplements, and sunlight exposure without the biological activity of vitamins D2 or D3, is rapidly hydroxylated by 25-hydroxylase in the liver to form 25-hydroxyvitamin D (25(OH)2D calcitriol), 152 which is synthesized and bound to allow the VD-binding protein to circulate, where it is hydroxylated by the kidneys to produce active 1α,25 dihydroxy VD (calcitriol). 153 The classical biological role of estriol as the active form of VD in controlling calcium and phosphate metabolism in bone health, 154 and previous studies have revealed that VD also regulates cell differentiation, strengthens the immune system, reduces oxidative stress and inflammation, and has neurotrophic effects in addition to its role in bone development.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Previous research has highlighted the involvement of VD in various body systems, regulating cell differentiation, enhancing the immune system, reducing oxidative stress and inflammation, and exerting neurotrophic effects. [75][76][77] Organisms in low VD states are more susceptible to oxidative stress and altered neurotransmitter signaling of dopamine and serotonin, leading to abnormal immune responses. 45 These immune responses have been shown to be metabolically abnormal in ASD.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Comparative clinical trials have shown that calcifediol at doses comparable to those of vitamin D3 induces a more rapid and larger increase in serum 25(OH)D concentrations. In terms of potency, calcifediol is between three and six times more potent than vitamin D3, a factor that may be beneficial when a rapid increase in vitamin D is needed [ 48 ].…”
Section: Recommendationmentioning
confidence: 99%